Compilation of an open-source traffic and CO2 emissions dataset for commercial aviation - Salgas, Antoine; Sun, Junzi; Delbecq, Scott; Planès, Thomas; Lafforgue, Gilles (Journal of Open Aviation Science, 2023)
The study of the environmental transition of the aviation sector calls for prospective traffic scenarios. Detailed traffic and emissions inventories are often needed to refine the available analyses and to enable the simulation of regionalised scenarios. In the past studies, these are generally based on commercial, proprietary traffic data, making their dissemination problematic and reducing the reproducibility of the science produced. Open-source alternatives do exist, but with limited geographical coverage. This paper presents a method to aggregate different sources of flight information, in order to obtain an open-source air traffic dataset for 2019. Then, missing flight information is identified and completed using an airline route database built from Wikipedia parsing and related socio-economic data. After that, several reference datasets are used to evaluate the accuracy of the extended open-source dataset. Despite varying accuracy for different routes, major traffic flows are reasonably well estimated at the country and continental levels. Finally, the CO2 emissions are obtained using an existing aircraft performance surrogate model, and the accuracies are examined compared to the results from previous studies.